Amygdala functional connectivity is associated with locus of control in the context of cognitive aging. (May 2017) - Ren, Ping; Anthony, Mia; Chapman, Benjamin P.; Heffner, Kathi; Lin, Feng
Abstract: Locus of control (LOC) measures the extent to which individuals perceive control over their lives. Those with a more "internal" LOC feel self-sufficient and able to determine important aspects of their own future, while those with a more "external" LOC feel that their lives are governed by events beyond their control. Reduced internal LOC and increased external LOC have been found in cognitive disorders, but the neural substrates of these control perceptions are yet unknown. In the present study, we explored the relationship between amygdala functional connectivity and LOC in 18 amnestic mild cognitive impairment (MCI) and age-, sex-, and education-matched, 22 cognitively healthy controls (HC). Participants completed cognitive challenge tasks (Stroop Word Color task and Dual 1-back) for 20 min, and underwent resting-state functional magnetic resonance imaging immediately before and after the tasks. We found significantly lower internal LOC and higher external LOC in the MCI group than the HC group. Compared to HC, MCI group showed significantly stronger positive associations between internal LOC and baseline right amygdala connections (including right middle frontal gyrus and anterior cingulate cortex), and stronger negative associations between internal LOC and change of these right amygdala connections. Across all participants, external LOC explained the relationships between associations of another set of right amygdala connections (including middle cingulate cortex and right superior frontal gyrus), both at baseline and for change, and performance in the cognitive challenge tasks. Our findings indicate that the right amygdala networks might be critical in understanding the neural mechanisms underlying LOC's role in cognitive aging. Highlights: MCI group had lower internal LOC while higher external LOC than HC. Higher internal LOC linked to greater baseline amygdala network in MCI. Higher internal LOC linked to less amygdala network change after challenge in MCI. External LOC explained amygdala network's link with cognitive performance.